A Study on The Formulation of Plant Matrix Tablets From Coarse Botanical Materials Using Cinnamon Bark and Areca Nut as The Model Botanical Materials - Veronica, Natalia; Ang, Xiu Hui; Ooi, Shing Ming; Liew, Celine Valeria; Heng, Paul Wan Sia (UI Scholars Hub, 2020)
Background: There is much interest in formulating botanical materials into tablets due to the compactness and ease of administration. However, tableting of coarse milled botanical materials poses a challenge due to poor tableting properties. Objective: To evaluate the feasibility of wet granulation to produce tablets from coarse milled botanical materials and to assess the effect of formulation on properties of the tablets. Materials and Methods: Cinnamon bark and areca nut were milled to obtain 1–2 mm particle size, which was subsequently used in wet granulation using maltodextrin solution as a granulating liquid. Two diluents were tried; microcrystalline cellulose (MCC) or mannitol at a different ratio to the botanical materials. Tablets were then produced from the granules and evaluated for tensile strength and surface roughness. Results: Tablets formulated with MCC had higher tensile strength than tablets formulated with mannitol. Additionally, granules prepared using mannitol were more friable than those with MCC. The effect of diluent to botanical material ratio was more prominently observed on tablet surface roughness. Tablets containing a higher ratio of botanical material had a rougher surface, which could have implications on the mouth-feel of the tablets. Conclusion: Wet granulation could be a viable pre-processing method to produce tablets from coarse milled botanical materials.